SPE Eastern Regional Meeting 2010
DOI: 10.2118/139083-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Carbon Dioxide Sequestration in Gas/Condensate Reservoirs

Abstract: Sequestration of CO 2 in depleted gas condensate reservoir has several advantages including enhanced hydrocarbon liquid recovery. Depleted gas condensate reservoirs have 13 times higher capacity than saline aquifers for CO 2 storage. The injection of CO 2 vaporizes the liquid that has been trapped in gas condensate reservoirs during the depletion process. This results in an increase in the pore space for storage purposes as well as enhanced economics due to additional liquid recovery. The improvements in liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The literature tends to focus either on maximising incremental production or on CO 2 storage capacity. However, simultaneous enhanced gas recovery (EGR), enhanced condensate recovery (ECR) and CO 2 storage may be feasible (Oldenburg, 2003;Oldenburg et al, 2004;Ramharack et al, 2010;Clemens et al, 2010). Following the European Trading Scheme, commercialising simultaneous EGR, EGR and CO 2 storage for all gas reservoirs is now being considered.…”
mentioning
confidence: 99%
“…The literature tends to focus either on maximising incremental production or on CO 2 storage capacity. However, simultaneous enhanced gas recovery (EGR), enhanced condensate recovery (ECR) and CO 2 storage may be feasible (Oldenburg, 2003;Oldenburg et al, 2004;Ramharack et al, 2010;Clemens et al, 2010). Following the European Trading Scheme, commercialising simultaneous EGR, EGR and CO 2 storage for all gas reservoirs is now being considered.…”
mentioning
confidence: 99%
“…al. [14] investigated the impact of CO 2 on gas condensate and found that drying effect can affect the phase diagram of gas condensate as shown in Figure 3.6. The shrinking of the two-phase envelope is reduction of cricondentherm and cricondenbar when CO 2 concentration increases.…”
Section: Fluid Composition Change By Flooding Processmentioning
confidence: 99%
“…14 Summarized results for different injection rates of combined gas dumpflood from 2 PV source gas reservoir with gas injection for well pattern 1…”
mentioning
confidence: 99%